Implikasi Nilai-Nilai Pendidikan Dalam Ayat Muhkamat Dan Mutasyabihat - Anggun Gia Rahma; Ameliya Putri; Durrinnafasati Ramadhani; Isma Nadiya; Sayyida Nafisa; H. Akhmad Dasuki (PT. Saha Kreasi Indonesia, 2025)
The Qur'an, as the greatest miracle that Allah bestowed upon the Prophet Muhammad, serves as a guide for human life. Within the Qur'an, there are verses that are easily understood with just one reading, also known as Muhkam verses, and there are also verses that require several methods to interpret them, and these verses are called Mutashabih. This research falls into the category of library research because it examines and analyzes the Muhkam and Mutashabih verses found in the Qur'an. This research shows: first, Muhkam verses are indeed mentioned as verses whose meaning can be understood in one reading, but this only applies to people who understand Arabic. For people who do not yet understand Arabic, a translation is needed. Second, the educational values that can be taken from the discussion of Muhkam and Mutashabih are religious values, tolerance values, wisdom values, hard work values, and responsibility values.